Characterization of starch amorphous solid dispersions manufactured via hot-melt extrusion by calorimetry and diffractometry - Duarte, Rita da Luz Franco de Paiva (2022)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2020, Universidade de Lisboa, Faculdade de Farmácia.